Morphological distinction of the Ophioderma Müller & Troschel, 1840 species (Echinodermata: Ophiuroidea: Ophiacanthida: Ophiodermatidae) from the Algerian west coast - Lebouazda, Zineb; Mezali, Karim; Khodja, Ihcene; Soualili, Dina Lila (Zootaxa, 2022)
Ophioderma longicaudum (Bruzelius, 1805) is a very common brittlestar in the Mediterranean Sea that had been considered as a complex of cryptic species since 2009. Recently, five species were separated from this complex, but they remain morphologically very close. The aim of this study is to attempt for the first time to identify the species of Ophioderma found at the Algerian west coast, using morphological and morphometric analysis. A total of 67 individuals of Ophioderma species were collected from three stations at the Mostaganem coast (Salamandre, Stidia-East and Stidia-West) during 2020 and 2021 and between 1.5 and 8 m depth. The morphological features showed a strong variability between the analysed individuals. Some resembled O. hybridum Stöhr, Weber, Boissin & Chenuil, 2020, others O. zibrowii Stöhr, Weber, Boissin & Chenuil, 2020 and some O. longicaudum (Bruzelius, 1805). Few resembled O. africanum Stöhr, Weber, Boissin & Chenuil, 2020 or O. guineense Greeff, 1882. The morphometric study displayed a significant discrimination between individuals and confirmed the morphological results suggesting that.